Effect of manganese and calcium deficiency on the growth and oxygen exchange of Scenedesmus intermedius cultured for successive generations - Adam, M S; Issa, A A (Folia microbiologica, 2000)
The green alga Scenedesmus intermedius was grown in synchronous culture under manganese or calcium deficiency for six successive generations. The growth rate, pigment and protein contents gradually decreased in comparison with the control. In Mn-deficient cells, the rate of oxygen evolution was sharply decreased. This inhibition was restored to normal in less than 1 h (40-60 min) by adding Mn salt to the suspension medium. In Ca-deficient cells, the inhibition of photosynthesis appears to be irreversible.
Keywords: Photosynthesis; časové faktory; Calcium; kultivační média; vápník; Oxygen; kyslík; Manganese; mangan; Chlorophyta; fotosyntéza; Time Factors; Culture Media